MAPPING OF TERMS ATTRIBUTED TO NURSING PHENOMENA IN THE WRITTEN DATA OF THE NURSING STAFF COMPONENTS - Patrícia Josefa Fernandes Beserra; Greicy Kelly Gouveia Dias; Wilma Cristina de Assis Nóbrega Nunes; Jaqueline Ferreira Araruna; Telma Ribeiro Garcia; Maria Miriam Lima da Nóbrega (Universidade Federal de Goias, 2003)
work aimed to identify the terms used by components of the nursing staff of the of the schoolhospital, in written patient clinical records, to designate phenomena of nursing; and to compare the terms identifiedwith those included in the Classification of Nursing Phenomena of the ICNP - Beta version. As the population ofstudy, it was considered all clinical records of the patients admitted in this service during the period of August/2001to January/2002; 167 clinical records that contained written data of components of the nursing staff constituted thesample. In the process, it was identification of 586 nursing phenomena. After the cross-mapping phase, it wasidentified 340 terms already included in the Classification of Nursing Phenomena of the ICNP - Beta version; and246 new possible terms to be included in the future.